A Research Study on the Use of Urdu Rhyme in Brahui Poetry - Nazeer, Hafsa; Sani, Liaquat Ali; Khatak, Khalid Mehmood (sourcecoder, 2023)
This research study delves into the intricate interplay of language and culture, focusing on the use of Urdu rhyme in Brahui poetry. Brahui, an ancient Dravidian language spoken predominantly in the Baluchistan region of Pakistan, has a rich tradition of oral and written poetry. However, in the absence of a dedicated Brahui rhyme dictionary and a formal system for Brahui terminology, the influence of Urdu, a more widely spoken and standardized language in the region, on Brahui poetry has been underexplored. Our investigation centres on the work of eight Brahui poets who contributed a total of 63 Brahui verses to our analysis. To our surprise, a significant number of these verses displayed a marked presence of Urdu rhyme schemes. This revelation has sparked concerns within the linguistic and literary community, as it raises questions about the preservation and evolution of the Brahui language and poetry. This study utilizes qualitative and quantitative methods to scrutinize the phenomenon of Urdu rhyme incorporation in Brahui poetry. We examine the reasons behind this linguistic convergence and its implications for the future of Brahui language and culture. Furthermore, we emphasize the need for the development of a comprehensive Brahui rhyme dictionary and a systematic framework for Brahui terminology. In conclusion, our research provides valuable insights into the complex dynamics of language, cultural influences, and the preservation of linguistic diversity. The findings contribute to the ongoing discourse on the intersection of language, culture, and identity, underscoring the urgent requirement for resources and strategies to safeguard the unique linguistic heritage of the Brahui people.